RANCANG BANGUN SISTEM MONITORING KETINGGIAN SAMPAH DAN TINGKAT GAS METANA PADA BAK SAMPAH BERBASIS IoT - Mudiarta, I Made; Janardana, I Gusti Ngurah; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 7 No 2 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i02.p4, 2020)
Garbage is often a problem, especially in big cities. The average amount of waste in Indonesia is 64 million tons / year, while the number of landfills in Indonesia is around 400 with a landfill capacity that can accommodate 233 kg / day. Not to mention the unpleasant odor and dirty city views cause discomfort. This is where a solution is needed by leading to the use of technology in an effort to create a clean environment by reducing the level of waste accumulation and reducing waste littered with the Internet of Things technology. This tool is able to monitor the height of waste and gas content via the web. The internet system uses the MCU Node module with energy supply from solar cells. Working voltage of the control system is 5V, a stepdown module is needed to reduce the battery voltage from 12V to 5V. Detection of the height of waste using a PING sensor and to determine the levels of methane gas using the sensor MQ-135. From testing at Student Center LT 4, it was found that the garbage accumulated on Saturday by 60 cm with 126 PPM methane gas levels that indicated unhealthy. This monitoring system can last up to 7 days because it uses solar cells, but this can experience changes due to the intensity of the sun.